Assessing usage of metacognitive online reading strategy and its relationship with students' comprehension achievement in the new norm / Saripah Anak Sinas ... [et al.] - Sinas, Saripah; Narasuman, Suthagar; Phek-Lin Sim, Sandra (Universiti Teknologi MARA, Kedah, 2022)
Online reading comprehension is increasingly becoming a high priority of education in the new norm. Thus, reading online texts without proper strategies would be challenging for students in an academic context. Students' success or struggle differs in their use of online reading strategies. This study aims to determine how students use the Metacognitive Online Reading Comprehension Strategies (MORCS) while reading online comprehension texts and whether there is any relationship between the MORCS and students' English language comprehension achievement. Ninety (90) students were sorted into three groups based on the types of training they received. The MORCS survey was distributed to students for feedback. A pre-test was administered before the training and a post-test was administered after the training was completed. Data were analysed using SPSS (version 24) descriptive analysis. Pearson's correlation analysis was conducted to examine if there was any significant relationship between the two variables. Results showed that the support strategy (M=3.97) and problem-solving strategy (M=3.86) were the most often used by respondents, followed by predicting strategy (M=3.85) and global strategy (M=3.84). The Pearson's correlation results showed a slight statistically significant relationship (r=0.054) between the MORCS and the students' online comprehension achievement after the intervention. This article ends with a discussion on the pedagogical implications and suggestions for further research in a related field.